Psychometric Properties of the English and Malay Version of the Adapted Schutte Emotional Intelligence Scale - Ahmad, Nor Aniza; Praveena, Sarva Mangala; Tee, Ker Shin (Frontiers in Psychology, 2022)
The study examines the psychometric properties of the adapted Schutte Emotional Intelligence Scale (A-SEIS) with 200 undergraduate students at the Universiti Putra Malaysia (UPM). Upon the permission, the researchers adapted the original instrument, SEIS by incorporating a new construct which is understanding of emotions and some ability-based items into the perceived emotions construct. The A-SEIS is a mixed (trait and ability) measure EI instrument that aims at assessing four important dimensions of EI, including perception of emotions, utilization of emotions, understanding of emotions, and management of emotions. The study investigated the content validity of the A-SEIS by using the content validity indexing (CVI). Three expert panels translated and back-translated the A-SEIS and rated the degree of relevance of every item based on the four-point scale provided in the content validation form. The exploratory factor analysis (EFA) methods were used to explore the underlying structure of the A-SEIS. The general validity testing of the adapted instrument was carried out in the framework of the structural equation modeling (SEM) approach by applying two iterations of confirmatory factor analysis (CFA), the first approach is the covariance-based SEM (CB-SEM) approach, followed by the partial least squares based SEM (PLS-SEM) using two different software: AMOS and smartPLS. Research findings concluded that the instrument is reliable and valid to be applied in tertiary education settings and future research.